2012
DOI: 10.1109/tciaig.2012.2204883
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Determinization in Monte Carlo Tree Search for the Imperfect Information Card Game Magic: The Gathering

Abstract: In this paper, we examine the use of Monte Carlo Tree Search (MCTS) for a variant of one of the most popular and profitable games in the world: the card game Magic: The Gathering (M:TG). The game tree for M:TG has a range of distinctive features, which we discuss here, and has incomplete information through the opponent's hidden cards, and randomness through card drawing from a shuffled deck. We investigate a wide range of approaches that use determinization, where all hidden and random information is assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…Knowledge about the hostile hand is usually inaccessible and thus there is a strong factor of uncertainty. With card pools of several hundreds or even thousands, this leads to a huge variety in the potential action space for the same game state, leading to an explosion in branching factors for TCGs, as Cowling et al [5] found. A common technique for MCTS approaches in situations with uncertainty is reducing the problem to a perfect information game through determinization.…”
Section: Monte Carlo Tree Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowledge about the hostile hand is usually inaccessible and thus there is a strong factor of uncertainty. With card pools of several hundreds or even thousands, this leads to a huge variety in the potential action space for the same game state, leading to an explosion in branching factors for TCGs, as Cowling et al [5] found. A common technique for MCTS approaches in situations with uncertainty is reducing the problem to a perfect information game through determinization.…”
Section: Monte Carlo Tree Searchmentioning
confidence: 99%
“…Due to these properties, TCGs are already used in academic work, such as using Monte Carlo Tree Search to cover uncertainty [5] or card selection [6]. Other work, such as HoningStone [7], focuses on the creative aspects of selecting card combos.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Gathering (Ward and Cowling, 2009;Cowling et al, 2012), a card game similar to Hearthstone. These approaches however usually solve subproblems of the game they are applied to, and not the game itself, through the abstraction of many variables.…”
Section: Machine Learning and Video Gamesmentioning
confidence: 99%